2022
DOI: 10.3389/fpsyg.2022.728733
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Social Support Received and Provided by Parents of Children, Adolescents and Young Adults With Cancer and Stress Levels and Life and Family Satisfaction

Abstract: IntroductionThe present study aims at analysing how social support received and provided by parents of children, adolescents and young adults (AYA) diagnosed with cancer, as well as their sociodemographic and clinical variables, affect those parents’ stress levels and life and family satisfaction.Materials and MethodsA total of 112 parents of children and AYAs who had been diagnosed with cancer and who received treatment in Malaga participated in the study. In the study, participated all parents who voluntaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…It was consistent with the previous ndings, in which parents in the US who had children with food allergic and had more social support were signi cantly associated with less parental monitoring, as well as a study in China reported that parents who had children with chronic conditions and had a relationship with friends, relatives, and neighbors increased parental mutuality, one component of EFM [31,48]. Better social support caused low levels of stress and burden, so it interfered with the management efforts and perceived fewer di culties, and predicted resilience [23,[49][50][51]. This result followed the previous research that stated that social support signi cantly predicted the resilience of Iranian parents with childhood cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…It was consistent with the previous ndings, in which parents in the US who had children with food allergic and had more social support were signi cantly associated with less parental monitoring, as well as a study in China reported that parents who had children with chronic conditions and had a relationship with friends, relatives, and neighbors increased parental mutuality, one component of EFM [31,48]. Better social support caused low levels of stress and burden, so it interfered with the management efforts and perceived fewer di culties, and predicted resilience [23,[49][50][51]. This result followed the previous research that stated that social support signi cantly predicted the resilience of Iranian parents with childhood cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire for the assessment of adjustment of parents of children with cancer Designed ad hoc by Hombrados-Mendieta and Martos-Méndez [44,45], this questionnaire measures situations that take place in different areas of parents' lives over the course of the child's cancer. It asks participants about the changes or disruptions brought about in different areas of their lives due to the child's cancer: partner (items 1 to 8), children (items 9 to 16), extended family (17 to 22), social relations (23 to 27), and economic and employment situations (items 28 to 30).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have analyzed some of the relations between the variables described, proving that social support received helps reduce parents' stress [43,44]. It has also been observed that both social supports received and provided by parents to their network increases their life satisfaction [43,44]. We also know that parents' adjustment relates negatively to social support received and provided, meaning that providing and receiving support reduces the impact of the disruptions they experience [45].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Social support encompasses significant resilience and a buffering factor against the negative implications of stress ( Schwartz-Attias et al, 2023 ). Stronger social support has been correlated with a higher level of well-being, which is reflected in life satisfaction, the cognitive component of well-being, and positive emotions, reflecting the emotional component of well-being ( Gise and Cohen, 2022 ; Melguizo-Garín et al, 2022 ), as well as lower levels of stress, hopelessness, and depression ( Makhoul Khoury et al, 2018 ). Little is known about the relation between social support and hope among parents of children with cancer.…”
Section: Introductionmentioning
confidence: 99%